FLUXO INTERNACIONAL DE FICÇÃO: A TELENOVELA BRASILEIRA NA BOLÍVIA - Costa, Ana Paula Silva Ladeira (2008)
The international flow of the Brazilian telenovela in Latin America has always faced competition from those traditional producers, Mexico and Venezuela. However, in Bolivia, the country of Spanish and native cultural tradition, the soap operas from Globo Network reach high registers of public. The main goal of that research was to figure out how that telenovela is watched by the Bolivian audience and the reason for this preference. Starting from the Uses and Gratifications theory, from Elihu Katz, a qualitative research was developed in Santa Cruz de la Sierra, with an application of questionnaires and accomplishment of interviews, looking for understanding the reception of the telenovelas in this city. The programming schedules of the most important networks of this country and its report of audience were also analyzed. The principal conclusions were: the success of the Brazilian telenovelas in Bolivia owes itself to the themes boarded; to the quality recognition of its production and to the televised images, as well as to the Brazilian network's selling strategies. The audience from this country use the content of the soap operas as instrument of information and learning and the style satisfies the necessity of evasion from reality and the affective necessities.